Experiments on the Nutrient Removal and Retention of an Integrated Pond System - Gál, Dénes; Szabó, Pál; Pekár, Ferenc; Kerepeczki, Éva; Váradi, László (Acta Agraria Debreceniensis, 2005)
A combined intensive-extensive fishpond system developed for the purification and re-use of intensive fishpond effluent water was studied during a three-year experimental period. The investigated pond system consists of five small-size intensive culture ponds of 1 ha total water surface area with 1.5 m water depth and a 20 ha extensive culture pond with 1.0 m average water depth. The water was recirculated between the intensive and extensive ponds with around 60 days retention time in the extensive treatment pond. Carbon, nitrogen and phosphorus budget and water purifying capacity were described and evaluated by means of regular measurements of nutrient concentrations in the water and sediment. During the three-year test period, 81.5% of organic carbon, 54.7% of nitrogen and 72.2% of phosphorus were retained by the system as a percentage of the total input of each nutrient. A significant amount of the total nitrogen input was removed by the harvested fish, which was much higher than in traditional fishponds or intensive fish culture systems. The efficiency of nutrient removal is clearly indicated by the 27.3% nitrogen assimilation. Only a small percentage of the total nutrient input was discharged into the environment during fish harvest, which was 9.0% for organic carbon, 13.2% for nitrogen and 12.1% for phosphorus. The combination of intensive and extensive fishponds with water recirculation resulted in significant reduction of nutrient discharge into the surrounding aquatic environment, primarily due to the high nutrient processing and retention capacity of the extensive fishpond ecosystem.